2010
DOI: 10.1039/b916422g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of proton dynamics and the proton transport pathway in choline dihydrogen phosphate using solid-state NMR

Abstract: Choline dihydrogen phosphate has previously been shown to be a good ionic conductor as well as an excellent host for acid doping, leading to high proton conductivities required for e.g., electrochemical devices including proton membrane fuel cells and sensors. A combination of variable-temperature 1 H solid-state NMR and 2D NMR pulse sequences, including 31 P and 13 C CODEX and 1 H BaBa, show that the proton conduction mechanism primarily involves assisted transport via a restricted three-site motion of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…well studied, initially prompted by the excellent proton conductivities of phosphoric-acid-based materials. The proton transport of this material is proposed to be facilitated by a three-fold rotation of the dihydrogenphosphate anion [15,16]. High proton diffusivities can be obtained after doping with acid [17].…”
Section: The Proton Conduction In Choline Dihydrogenphosphate [Cholinmentioning
confidence: 99%
“…well studied, initially prompted by the excellent proton conductivities of phosphoric-acid-based materials. The proton transport of this material is proposed to be facilitated by a three-fold rotation of the dihydrogenphosphate anion [15,16]. High proton diffusivities can be obtained after doping with acid [17].…”
Section: The Proton Conduction In Choline Dihydrogenphosphate [Cholinmentioning
confidence: 99%
“…Strongly kosmotropic anions such as dihydrogen phosphate (dhp) and a chaotropic cation such as choline are expected to stabilize proteins (20). However, choline dhp is actually a white solid and not a room temperature ionic liquid (22). Patterns of protein unfolding and protein aggregation have been compared for ribonuclease A in choline dihydrogen phosphate and two imidazolium ionic liquid solutions from 0 to 4 M. The choline dihydrogen phosphate enhanced thermostability while the 1-ethyl-3-methylimidazolium dicyanide was a strong denaturant (23).…”
Section: Introductionmentioning
confidence: 99%
“…ChoDHP is the most hydrophilic IL in this study, although it is formed by hydrophilic cation and hydrophilic anion based on their Log P (Table 2). Previous studies have shown that ChoDHP has an extended network of hydrogen bonding particularly though the DHP anions containing two protons (Fujita et al, 2009; Cahill et al, 2010). The proton of DHP anion transports via the reorganization of hydrogen bonds (Rana et al, 2010), and it is possible that this infinite and complicated network of hydrogen bonds hinder the interaction with water, compared with other ILs in this study.…”
Section: Resultsmentioning
confidence: 99%